Analysis of percent inter-temporal changes in foreign investment inflow by sectors in Ukrainian economy - Olga Nehrych (Cхід, 2013)
Analysis of foreign investment inflow by sectors in Ukrainian economy during preceding 10 years is described in the article. Also percent inter-temporal changes in foreign investment inflow by sectors are formed and analyzed here. This analysis shows that in spite of foreign direct investment amount absolute figure vivid rise by years practically in every sector, percent inter-temporal changes in foreign investment inflow by these sectors look different. Also recommendations of involving investment policy improvement are proposed.